(untitled) (International Journal of Ayurveda and Pharma Research, 2023)
Mutrakriccha is a big health concern these days as a result of infection, an irregular lifestyle, and poor eating habits. Mutra marga gat Strotas defined Ayurveda as being related to urinary tract infections. Mutrakriccha is a sickness documented in nearly all Ayurvedic classics in which a patient has severe and uncomfortable burning micturition. Mutrakriccha is classified into eight types, each with its own set of signs and symptoms, and may be linked to dysuria. Antibiotics are now widely used to treat the condition. However, many side effects and antibiotic resistance developed. As a result, treating the condition becomes more complicated. In Mutrakriccha Vyadhi, Gokshur is a more effective medicine. The medications used in the treatment of Mutrakriccha have been documented in numerous Ayurvedic texts. I conducted a 90-day Mutrakriccha clinical study on 20 participants. The outcomes are as follows: For B.D., these 20 patients were treated with Gokshur Mool Churna. One patient dropped out of the experiment. Out of the 19 patients who completed treatment, 12 (63.16%) were cured, 5 (26.32%) were moderately improved, and 2 (10.53%) were mildly improved.